Analysis of Performance Measurement Using the Value For Money Method at Departments in the City of Bogor - Serli Margareta; Ade Budi Setiawan; Warizal; Yuppy Triwidatin (Indonesian Journal of Advanced Research, 2023)
Performance in government agencies is very important to know how well programs and activities are implemented each year. This research was conducted to measure the performance of government agencies using the Value For Money method at the Bogor City Transportation Service. This research aims to determine the performance of the Bogor City Transportation Department for the 2019-2021 period in terms of three elements, namely; economy, efficiency and effectiveness. The research design with the data used is LAKIP and LRA for the 2019-2021 period with data analysis tools using the VFM method. The research results show that the performance of the Bogor City Transportation Department for the 2019-2021 period of performance measurement is categorized as very good. Based on the VFM method, in terms of the economic level in 2019-2021, it is categorized as very economical, in terms of the efficiency level in 2019-2021, it is categorized as inefficient, in terms of the level of effectiveness of the performance measurement results in 2019-2021, it is categorized as very effective.